Homogeneous distribution of carriers in the conducting planes by Zn substitution at Cu sites in Cu0.5Tl0.5Ba2Ca3Cu4O12-d superconductors - Mumtaz, M.; Khan, Nawazish A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The effect of suppression of antiferromagnetic order and charge stripes formation mechanism, by Zn3d10 (S = 0) substitution at Cu3d9 (S = 1/2) sites in CuO2 planes of Cu0.5Tl0.5Ba2Ca3Cu4O12–δ, on superconductivity parameters is demonstrated. If antiferromagnetism and charge stripes have some role in bringing about superconductivity at a particular temperature, the doping of nonmagnetic Zn impurity would destroy it and hence the superconductivity.However we have observed enhanced superconducting properties with the increase of Zn doping in Cu0.5Tl0.5Ba2Ca3Cu4O12–δ superconductor. The decreased c-axis length with the increase of Zn doping improves interlayer coupling and hence the three-dimensional conductivity in the unit cell. The role of charge carriersin CuO2 planes of Cu0.5Tl0.5Ba2Ca3Cu4–yZnyO12–δ in bringing about superconductivity has also been explained.